Academic Information System Audit Using the COBIT 5 Framework Deliver, Service, and Support (DSS) Domain - Ramadani, Zahira Naswa; Safana, Alya; Lestari, Bunga Citra; Wardhani, Neng Sri (CV Raskha Media Group, 2025)
The use of information technology in higher education is a strategic necessity to support the effectiveness and efficiency of academic processes. One form of its use is the Academic Information System (SIAKAD) as a means of managing academic data, administrative services, and providing information for students, lecturers, and management. However, the implementation of SIAKAD does not automatically guarantee that its management is in accordance with the principles of good information technology governance. Therefore, an evaluation through an information system audit is needed to assess performance, service quality, and system control. his study aims to audit the Academic Information System using the COBIT 5 framework with a focus on the Deliver, Service, and Support (DSS) domain. This domain was chosen because it is directly related to the delivery of information technology services, operational support, incident management, security, and service continuity. The research method used is mixed methods with a qualitative and quantitative approach, through observation, interviews, and the distribution of questionnaires compiled based on the COBIT 5 Process Assessment Model (PAM). The results of the study show that all processes in the DSS domain are at capability level 4 (Predictable Process). This indicates that IT service management has been running consistently and in a controlled manner. However, continuous improvement is still needed so that the process can reach the optimal capability level.